(untitled) (International Journal of Environmental Sciences, 2025)
Rapid urban expansion and lifestyle changes have intensified challenges in municipal solid waste management, particularly in developing regions where inefficiencies in collection and disposal exacerbate environmental impacts. In Mysuru, Karnataka, approximately 450 tonnes of solid waste are produced daily across 65 wards, and the existing collection system is challenged by long collection routes, high fuel consumption, and the need to utilize landfills. This study aimed to assess current collection habits and subject them to Geographic Information System (GIS)-informed spatial optimization to minimize the travel on two levels: distance and fuel, while lowering emissions. ArcGIS Network Analyst was combined with high-resolution satellite imagery, municipal records, and GPS tracking data of collection vehicles to model and optimize routes in five wards. Outcomes showed significant gains in efficiency with travel distances minimized by 18.47% in Ward 6 (Gokulam), 19.95% in Ward 42 (K G Koppal), 27.01% in Ward 47 (Kuvempunagar), 27.9% in Ward 51 (Agrahara), and 42.11% in Ward 43 (T K Layout). Such gains equated to 1.2–1.7 liters of fuel savings daily and carbon dioxide decreases between 2.5 and 4.4 kg per ward. These results show that a GIS-based optimization can offer a quantitative process of attaining greater waste collection efficiencies and, at the same time, enable a path towards climate mitigation and sustainable urban governance. These results underline that route optimization is a climate mitigation approach that mitigates the use of fossil fuels, decreases greenhouse gas emissions, and ensures allied commitment to environmental sustainability objectives within the Sustainable Development Goals.